Blended Learning Model in Elementary School : Systematic Literature Review - Muhamad Suhardi (Journal of Psychology and Instruction, 2025)
Blended learning model is an approach that combines face-to-face learning with online learning in an integrated manner, allowing for a more flexible and adaptive learning experience. This research aims to analyze learning management in the implementation of Blended Learning model in elementary school through Systematic Literature Review (SLR) approach. Data were collected from seven relevant scientific articles, obtained through a search on Google Scholar in March 2025 with a publication range of 2020-2024. The search began with the keyword "Learning Management", resulting in 31,700 articles, then focused with the addition of the words "Blended Learning Model" and "in Elementary School" until it was filtered to 147 articles. Selection based on inclusion criteria resulted in seven articles that were analyzed further. The results showed that the success of learning management in blended learning is determined by teacher readiness, stakeholder support, and appropriate technology utilization. The three main aspects found include the effectiveness of learning planning and implementation, the role of social environment in supporting students, and the importance of innovation in digital-based evaluation. The implication of this research confirms that blended learning can be a sustainable learning strategy in primary schools if supported by adaptive management, flexible curriculum, and continuous teacher training.